Making the Decision to Participate in Organized After-School Activities: Perspectives From Mexican-Origin Adolescents and Their Parents. Issue 3 (May 2022) - Lin, Alex R.; Dawes, Nickki P.; Simpkins, Sandra D.; Gaskin, Erin R.
The decision to enroll in organized after-school activities involves a gradual negotiation of adolescents' independence between family members who can hold contrasting views on adolescents' autonomy. Furthermore, less is known about the culturally grounded nature of this decision-making process generally observed among the Latinx community, especially those from immigrant backgrounds, where adolescents may serve as the cultural brokers to help their families navigate through certain cultural barriers outside the home. In this study, we analyzed semi-structured interviews from a diverse group of 34 Mexican-origin parent-adolescent dyads living in a Southwest metropolitan area. Results indicate that decision making on organized activities can occur across multiple distinct pathways that reflect unilateral and mutual decision making based on the parents' and adolescents' level of involvement. The adolescents' strong role as cultural brokers not only reflects a critical role of helping their parents navigate through the cultural barriers of the after-school world but can also empower them to have a greater voice within a context of positively developing a more equal basis of decision making in the parent-child dynamic. Findings from this study highlight the rich diversity among Mexican-origin families and can help further strengthen organized activities in being responsive to the diverse cultural practices of families.